A fatigue life estimation approach considering the effect of geometry and stress sensitivity. (April 2021) - Li, Zhenlei; He, Yushu; Xu, Guoqiang; Shi, Duoqi; Yang, Xiaoguang
Highlights: A double-slope method was proposed to calculate the critical distance. An elastic geometrical feature factor was defined to account for stress concentration. A stress sensitivity factor was proposed to assess the plasticity effect. A fatigue life estimation approach was proposed with a good accuracy. Abstract: This paper proposes a notch fatigue life prediction model to account for the effect of geometry and applied stress. A double-slope method was proposed to calculate the critical distance, which was utilized to determine the damage zone of geometrically complex structures. An elastic geometrical feature factor was defined to characterize the stress concentration. Considering the effect of applied stress on low cycle fatigue (LCF) life, a stress factor was proposed. A fatigue life estimation approach was established by introducing the elastic geometrical feature factor, the stress factor and an improved critical distance method. This model was validated by the experimental results of notched specimens with various geometries and loadings. Compared with the existing models, the proposed model provides a better accuracy.